Experimental investigation of ignition delay and laminar burning velocity of HVO/RP-3 blends as a drop-in aviation fuel under extended operating conditions - Linlin Gu; Xunkai Hu; Chongyang Liu; Dongdong Qi; JingYu Ran; Zhongqing Yang (Fuel, 2027)

Artificial intelligence-driven food labels: Technological convergence, application innovation, and sustainable future - Linlin Zhao; Xingyu Chen; Wenqin Gu; Huinan Jiang; Bimal Chitrakar; Xiangren Meng (Trends in Food Science & Technology, 2026)

Characteristics of overpressure and thermal effects of methane–air explosions in tunnels - Linlin Gu; Zhenjing Nie; Yi Li; Zhen Wang; Chuyuan Huang; Xianfeng Chen (Fuel, 2026)

Comparative metabolomics reveals distinct metabolic profiles and in vitro activities of fermented noni juice from Samoa and China's Hainan - Qianjin Ni; Meimei Nie; Linlin Han; Mingfei Gu; Lingming Xiong; Yayuan Xu; Lei Feng; Liying Niu; Runqiang Yang; Dajing Li; Zhuqing Dai (Food Chemistry, 2026)

Carbon dots/konjac glucomannan/starch anti-freezing gel: development and cryoprotective coating for beef preservation - Linlin Zhao; Zeyue Zhao; Wenqin Gu; Huinan Jiang; Hao Xu; Suqing Sun; Xiangren Meng (Food Research International, 2026)

A nanoengineered strategy combining deep oxygenation and immunogenicity regulation to unleash the power of anti-tumor immunity - Gang Cheng; Linlin Tao; Nian Huang; Xiaoxiao Hu; Mengmeng Yang; Fangnan Lv; Nan Yang; Siyuan Meng; Zuhang Xing; Boyu Gu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

Damage and Creep Response of Tunnel Lining Concrete at Elevated Temperatures - Linlin Yao; Linlin Gu; Zhen Wang; Zhiquan Huang; Fei Gao (Geotechnical and Geological Engineering, 2026)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Experimental study on mechanical properties of a new duplex stainless steel for structures under different temperature-stress combination paths - Shuobiao Li; Zhen Wang; Wenqi Ding; Qingzhao Zhang; Linlin Gu (Engineering Structures, 2025)

Ion channels: beyond native mass spectrometry - Ronald J. Quinn; Yushu Gu; Miaomiao Liu; Linlin Ma (Phytochemistry Letters, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Mutual influence of bubble evolution and seepage flow in heterogeneous porous matrices - Linlin Gu; Shicai Sun; Rundong Zhang; Rongtao Yan; Yonghao Yin; Guanru Gong (Gas Science and Engineering, 2025)

Optimized Soil Nitrogen Management for Enhanced Photosynthetic Efficiency and Yield in High-Quality Japonica Rice in the Taihu Lake Region - Yunsheng Song; Yulin Xie; Minghui Dong; Fei Chen; Xiuliang Jin; Yajie Hu; Junrong Gu; Peifeng Chen; Yongliang Zhu; Linlin Shi; Yixiao Wang (International Journal of Plant Production, 2025)

Inter-trophic networks reveal the central role of methanogens in deposited estuarine soils - Linlin Wang; Xiongfeng Du; Wenli Shen; Songsong Gu; Zhaojing Zhang; Zheng Zhang; Baohua Xie; Guangxuan Han; Ye Deng (Soil Ecology Letters, 2025)

In2O3 modification mitigates Jahn-Teller effect in LiMn2O4 enhancing lithium extraction efficiency and stability - Linlin Chen; Linjing Fan; Delin Lan; Jun Gu; Chen Xiaojun; Haiyan Ji; Yanhong Chao; Peiwen Wu; Wenshuai Zhu (Chemical Engineering Journal, 2025)

Sulfur-vacancy-enriched ZnIn2S4 mediates efficient charge transfer for hydrogen evolution from lignocellulose photoreforming - Jiang He; Zhongqing Yang; Ziqi Wang; Linlin Gu; Jiaqi Qiu; Jingyu Ran (Chemical Engineering Journal, 2025)

Effects of nitrogen fertilization on nitrogen metabolism and grain protein in premium-tasty japonica rice - Yunsheng Song; Minghui Dong; Yajie Hu; Linlin Shi; Junrong Gu; Yuxuan Wang; Shikun Wang; Penghui Cao; Yajie Yu; Yongliang Zhu; Yulin Xie; Zhongying Qiao; et al. (Cereal Research Communications, 2024)

A novel flow control method suppressing tip leakage vortex of a hydrofoil applied for ducted devices - Fadong Gu; Lei Shi; Xi Shen; Guangjian Zhang; Linlin Geng; Desheng Zhang; B.P.M. (Bart) van Esch (Ocean Engineering, 2024)

Transcriptomic analysis uncovers a biphasic response to precocious Eimeria acervulina infection in chicken duodenal tissue - Ning Zhang; Jie Liu; Yuanyuan Zhang; Linlin Chen; Sixin Zhang; Xianyong Liu; Xinming Tang; Xiaolong Gu; Shiyi Chen; Xun Suo (Veterinary Parasitology, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

Response of a Coral Reef Sand Foundation Densified through the Dynamic Compaction Method - Linlin Gu; Weihao Yang; Zhen Wang; Jianping Wang; Guanlin Ye (Journal of Marine Science and Engineering, 2024)
Dynamic compaction is a method of ground reinforcement that uses the huge impact energy of a free-falling hammer to compact the soil. This study presents a DC method for strengthening coral reef foundations in the reclamation area of remote sea islands. Pilot tests were performed to obtain the design parameters before official DC operation. The standard penetration test (SPT), shallow plate-load test (PLT), and deformation investigation were conducted in two improvement regions (A1 and A2) with varying tamping energies. During the deformation test, the depth of the tamping crater for the first two points’ tamping and the third full tamping was observed at two distinct sites. The allowable ground bearing capacity at two disparate field sites was at least 360 kPa. The reinforcement depths were 3.5 and 3.2 m in the A1 and A2 zones, respectively. The DC process was numerically analyzed by the two-dimensional particle flow code, PFC2D. It indicated that the reinforcement effect and effective reinforcement depth were consistent with the field data. The coral sand particles at the bottom of the crater were primarily broken down in the initial stage, and the particle-crushing zone gradually developed toward both sides of the crater. The force chain developed similarly at the three tamping energies (800, 1500, and 2000 kJ), and the impact stress wave propagated along the sand particles primarily in the vertical direction.

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

Quantitative distribution and quantized ecological threat of microplastics in farmland: Shanghai as an example - Zhengwen Li; Zhaofeng Song; Linlin Qiu; Yan Cao; Hairong Gu; Zhenqi Wang; Xiang Liu; Xiaoyong Qian (Journal of Hazardous Materials, 2024)

Acid-assisted ultrasonic preparation of nitrogen-doped MXene quantum dots for the efficient fluorescence “off-on-off” detection of Zn(II) in water and oxalic acid in vegetables - Jinwen Yang; Linlin Chen; Jie Qi; Feili Luo; Lin Li; Honghong Wu; Feifei Cao; Jiangjiang Gu (Food Chemistry, 2024)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

Synergistic strategy based on mild phototherapy and deep tumor hypoxia reversal comprehensively remodels the tumor microenvironment for improved immunotherapy - Linlin Tao; Gang Cheng; Fangnan Lv; Ruiqi Wang; Nan Yang; Zuhang Xing; Boyu Gu; Siyuan Meng; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2023)

Experimental study on hydrogen production characteristics of kaolin supported Ni catalyzed by steam gasification of citrus peel - Linlin Gu; Mingnv Guo; Jiang He; Zhongqing Yang (Fuel, 2023)

Effect of bubbles on the gas–water migration during gas hydrate dissociation by depressurization - Shicai Sun; Zhendong Yang; Linlin Gu; Haifei Lin; Changxing Zhang (Fuel, 2023)

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Gas hydrate dissociation by depressurization along with ice occurrence and sand migration - Shicai Sun; Linlin Gu; Zhendong Yang; Haifei Lin; Changxing Zhang (Gas Science and Engineering, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Influence of Initial Stress and Deformation States on the Shear Creep Behavior of Rock Discontinuities with Different Joint Roughness Coefficients - Zhen Wang; Linlin Gu; Qingzhao Zhang; Bo-An Jang (Rock Mechanics and Rock Engineering, 2021)

Consolidation Pressure Consequences on the Soil Structure of Artificial Structured Marine Clay: Macro and Micro Evaluation - Usama Khalid; Guan-lin Ye; Santosh Kumar Yadav; Annan Zhou; Linlin Gu (Geotechnical and Geological Engineering, 2021)

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Creep characteristics and prediction of creep failure of rock discontinuities under shearing conditions - Zhen Wang; Linlin Gu; Qingzhao Zhang; Songlin Yue; Guokai Zhang (International Journal of Earth Sciences, 2020)

Evaluation of Genomic Selection for Seven Economic Traits in Yellow Drum (Nibea albiflora) - Guijia Liu; Linsong Dong; Linlin Gu; Zhaofang Han; Wenjing Zhang; Ming Fang; Zhiyong Wang (Marine Biotechnology, 2019)
Yellow drum ( Nibea albiflora ) is an important maricultural fish in China, and genetic improvement is necessary for this species. This research evaluated the application of genomic selection methods to predict the genetic values of seven economic traits for yellow drum. Using genome-wide single-nucleotide polymorphisms (SNPs), we estimated the genetic parameters for seven traits, including body length (BL), swimming bladder index (SBI), swimming bladder weight (SBW), body thickness (BT), body height (BH), body length/body height ratio (LHR), and gonad weight index (GWI). The heritability estimates ranged from 0.309 to 0.843. We evaluated the prediction performance of various statistical methods, and no one method provided the highest predictive ability for all traits. We then evaluated and compared the use of genome-wide association study (GWAS)–informative SNPs and random SNPs for prediction and found that GWAS-informative SNPs obviously increased. It only needed 5 and 100 informative SNPs for LHR and BT to achieve almost the same predictive abilities as using genome-wide SNPs, and for BL, SBI, SBW, BH, and GWI, about 1000 to 3000 informative SNPs were needed to achieve whole-genome level predictive abilities. It can be concluded from the test results that breeders can use fewer SNPs to save the breeding costs of genomic selection for some traits.

Luteolin decreases the yield of influenza A virus in vitro by interfering with the coat protein I complex expression - Haiyan Yan; Linlin Ma; Huiqiang Wang; Shuo Wu; Hua Huang; Zhengyi Gu; Jiandong Jiang; Yuhuan Li (Journal of Natural Medicines, 2019)

Seismic behavior of breakwaters on complex ground by numerical tests: Liquefaction and post liquefaction ground settlements - Linlin Gu; Feng Zhang; Xiaohua Bao; Zhenming Shi; Guanlin Ye; Xianzhang Ling (Earthquake Engineering and Engineering Vibration, 2018)

Settlement mechanism of piled-raft foundation due to cyclic train loads and its countermeasure - Linlin Gu; Guanlin Ye; Zhen Wang; Xianzhang Ling; Feng Zhang (Earthquake Engineering and Engineering Vibration, 2017)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)